Blue light-promoted photolysis of aryldiazoacetates. Issue 22 (24th May 2018) - Jurberg, Igor D.; Davies, Huw M. L.
Abstract : Aryldiazoacetates can undergo photolysis under blue light irradiation (460–490 nm) at room temperature and under air in the presence of numerous trapping agents, such as styrene, carboxylic acids, amines, alkanes and arenes, thus providing a straighforward and general platform for their mild functionalization. Abstract : Aryldiazoacetates can undergo photolysis under blue light irradiation (460–490 nm) at room temperature and under air in the presence of numerous trapping agents, such as styrene, carboxylic acids, amines, alkanes and arenes, thus providing a straighforward and general platform for their mild functionalization.